Design and implementation of an automatically aligned solar tracking system - Abu Sneineh, Anees; Salah, Wael A. (Institute of Advanced Engineering and Science, 2019)
This paper presents the design and implementation of a closed-loop solar tracker system. The demand for clean energy sources has increased along with the rising demand for electrical energy and the increasing amount of environment pollution triggered by fuel consumption. Among these sources, solar energy is considered the most feasible given its wide availability and easy operation in different environments. The main purpose of this study is to maximize the generated photovoltaic power and reduce CO2 emissions by designing an efficient and low-cost solar tracking system. An aligned closed-loop solar tracker is designed and constructed to achieve the best accuracy. The proposed system shows more freedom in its movement to overcome the problems associated with the tilt of the frame-holder. A PIC microcontroller based on the Flowcode programming language is used, the position feedback is detected by using a photo-sensor, and the H-Bridge driver is used to control two DC motors. According to the experimental results, the proposed system shows significant improvements in efficiency compared with stationary solar tracking systems.